Penyuluhan Pentingnya Etika Bermedia Sosial Bagi Seorang Muslim Guna Mencegah Penyalahgunaan Dalam Bermedia Sosial - Rosita Putri, Ari; Budiani, Herta; Khadijah, Lala; Nur Aeni, Ani (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2022)
The development of technology that is growing rapidly makes information easily spread and accepted. The development of technology which is accompanied by the presence of increasingly varied social media provides changes in social life. This is a digital era where all activities are related to digital. Everything that is done is inseparable from social media. Islam is a religion that likes peace and does not like division, therefore when using social media as a Muslim, you must pay attention to the applicable ethics and adab. Therefore, the researcher conducted outreach activities on the importance of social media ethics for a Muslim. The purpose of the counseling activity is to educate the importance of ethics in using social media, especially for a Muslim